PENGARUH PROMOSI "11.11 WONDER SALE" SOCIOLLA TERHADAP KEPUTUSAN PEMBELIAN MAKEUP DI ERA PANDEMI (Survei Pada Followers Instagram Sociolla) - Vira Zania (2021)
This study aims to determine the magnitude of the influence of Sociolla's "11.11 wonder sale" promotion on Instagram social media on Purchase Decisions Makeup in the Pandemic Era. The relevant theory in this research is SR Theory (Stimulus, Response). The population of this study is the followers of the sociolla Instagram account with a sample of 100 respondents. The correlation results can be interpreted as the "11.11 wonder sale" promotion is strongly related to the consumer's decision to purchase makeup in the pandemic era. Based on the results of the calculation of determination, the results of the magnitude of the influence of the X variable on the Y variable which can be interpreted that the "11.11 wonder sale" promotion has an influence with "medium" strength in influencing the decision to purchase makeup in the pandemic era. These results are supported by the results of hypothesis testing, namely the promotion of "11.11 wonder sale" sociolla which affects the decision to purchase makeup in the pandemic era. The results of the SR theory in this study are in line. It is evident that the respondents were influenced by the message conveyed by Sociolla in the form of the promotion of "11.11 wonder sale" so that they were able to make the public decide to buy makeup in the pandemic era.